Genome-Wide Analysis of Human Preimplantation Aneuploidy - Treff, Nathan R. (Seminars in Reproductive Medicine, 2012)
An exciting era in preimplantation genetic diagnosis (PGD) is emerging with the adaptation and development of new high throughput genome-wide methodologies for the evaluation of aneuploidy. In fact, many promising preclinical studies and clinical trials involving comprehensive chromosome screening (CCS) have renewed clinician interest in the use of PGD for aneuploidy screening as an embryo selection tool to improve the success of in vitro fertilization (IVF). This review will provide an overview of the basic underlying features and applications of the growing number of platforms and strategies for preimplantation genome-wide analysis of aneuploidy.
Keywords: whole genome amplification; comprehensive chromosome screening; preimplantation genetic diagnosis; aneuploidy